2013
DOI: 10.1177/0886260512475310
|View full text |Cite
|
Sign up to set email alerts
|

Violence in Adulthood and Mental Health

Abstract: The aim of this study was to describe perceived abuse in adult Spanish and Ecuadorian women and men and to assess its association with mental health. A population-based survey was conducted in Spain in 2006. Data were taken from a probabilistic sample allowing for an equal number of men and women, Spaniards and Ecuadorians. Mental disorder was measured with the General Health Questionnaire-28. The nine questions on exposure to physical, sexual, and psychological abuse during the previous year were self-adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The results of this study are in line with those of the previous publications on these population-based samples showing that the psychological violence was the form experienced more frequently, with more than half of those interviewed having reported an experience of this form of violence in the past 12 months in Italy [ 29 , 30 ]. In concert with past research, an unknown person was found to be the most predominant offender among those victimized [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are in line with those of the previous publications on these population-based samples showing that the psychological violence was the form experienced more frequently, with more than half of those interviewed having reported an experience of this form of violence in the past 12 months in Italy [ 29 , 30 ]. In concert with past research, an unknown person was found to be the most predominant offender among those victimized [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, global estimates indicate that about 35% women have experienced either physical and/or sexual intimate partner violence or nonpartner sexual violence in their lifetime [ 31 ]. The findings regarding the higher frequency of violence in women compared to male was observed in previous studies [ 16 , 18 , 29 , 32 ]. This disturbing finding suggests that there is plenty of room for action that should be activated as soon as possible, tailored for reducing this value.…”
Section: Discussionsupporting
confidence: 75%
“…Another finding was that being foreign-born and experiencing lack of social support were associated with DV exposure, which confirms findings from previous studies. 18 , 26 , 37 The association between being foreign-born and risk of DV has previously been suggested to be explained by social and economic inequalities, 37 but in this study, associations that included the variables social support and financial problems remained in the multivariate analyses. However, stronger associations were found between social support and DV in both sexes and among women, financial problems was also associated with DV.…”
Section: Discussionmentioning
confidence: 74%
“…Research on gender-based differences in the negative impacts of experience of IV on mental health are inconclusive. While research has shown that women are more likely to suffer from mental health symptoms associated with the experience of violence [ 6 , 40 , 41 ], there are some studies suggesting that the impacts of IV on mental health outcomes do not vary by gender [ 12 , 15 , 42 ]. In contrast, some studies have shown that the impacts of IV on mental health are more pronounced in men [ 13 , 43 ].…”
Section: Discussionmentioning
confidence: 99%